2017
DOI: 10.1128/genomea.00750-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Getah Virus Strains Isolated from Horses in 2016 in Japan

Abstract: Getah virus is mosquito-borne and causes disease in horses and pigs. We sequenced and analyzed the complete genomes of three strains isolated from horses in Ibaraki Prefecture, eastern Japan, in 2016. They were almost identical to the genomes of strains recently isolated from horses, pigs, and mosquitoes in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…GETV infections can cause fever, rashes, and edema of the hindlegs in horses ( 15 ), fetal death and reproductive disorders in pigs ( 16 ) as well as fever, anorexia, depression, neurologic symptoms, and death in foxes ( 17 ). GETV infections in horses and pigs have been reported several times in Japan since the 1970's ( 18 21 ), and the outbreak of GETV infections in horses were reported in 1990 in India ( 22 ). In China, GETV is widely distributed in 15 provinces ranging from the southwest to northern areas of China since it was first identified from mosquitos in Hainan province, and it has caused several outbreaks in animals in recent years ( 2 , 7 , 17 , 23 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…GETV infections can cause fever, rashes, and edema of the hindlegs in horses ( 15 ), fetal death and reproductive disorders in pigs ( 16 ) as well as fever, anorexia, depression, neurologic symptoms, and death in foxes ( 17 ). GETV infections in horses and pigs have been reported several times in Japan since the 1970's ( 18 21 ), and the outbreak of GETV infections in horses were reported in 1990 in India ( 22 ). In China, GETV is widely distributed in 15 provinces ranging from the southwest to northern areas of China since it was first identified from mosquitos in Hainan province, and it has caused several outbreaks in animals in recent years ( 2 , 7 , 17 , 23 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the subsequent 30 years, no GETV outbreaks were observed among racehorses in Japan. However, GETV outbreaks occurred suddenly from 2014 to 2016 at the Miho Training Center among racehorses which had been vaccinated against GETV [ 2 , 18 , 20 ].…”
mentioning
confidence: 99%
“…One study reported that GETV was unexpectedly isolated from Culex tritaeniorhyncus mosquitoes at high minimum infection rates in Nagasaki Prefecture in 2012 [ 13 ]. This GETV strain 12IH26 isolated from mosquitoes in Nagasaki Prefecture is phylogenetically related to the GETV strains that caused an epidemic among racehorses in 2014 and 2016 [ 20 ], being also closely related to Chinese and South Korean strains, rather than the Kochi/01/2005 strain reported in 2005, which is considered a Japanese domestic strain [ 25 ]. Another study reported an epidemic of GETV infection among wild boar populations in Japan in 2012 [ 14 ].…”
mentioning
confidence: 99%